Proposal for Observing the Unruh Effect using Classical Electrodynamics - Cozzella, Gabriel [UNESP]; Landulfo, André G. S.; Matsas, George E. A.; Vanzella, Daniel A. T. (American Physical Society (APS), 2017)
Although the Unruh effect can be rigorously considered as well tested as free quantum field theory itself, it would be nice to provide experimental evidence of its existence. This is not easy because the linear acceleration needed to reach a temperature 1 K is of order 1020 m/s2. Here, we propose a simple experiment reachable under present technology whose result may be directly interpreted in terms of the Unruh thermal bath. Instead of waiting for experimentalists to perform it, we use standard classical electrodynamics to anticipate its output and fulfill our goal.